Prediction of endotracheal tube size in the pediatric age group by ultrasound: A systematic review and meta-analysis - Bhavna Gupta; Pallavi Ahluwalia (Wolters Kluwer Medknow Publications, 2022)
Anatomical differences in the airway in pediatric patients, compared to adults pose many challenges during endotracheal intubation, such as selecting the proper sized endotracheal tube (ETT) during intubation. Our primary objective was to assess how accurate is ultrasound (US) co-relation in comparison to standard age-based formulas in pediatric patients. Meta-analysis was registered in PROSPERO 2020, CRD42020220041. Online literature available in PubMed, Cochrane, and Embase, Goggle scholar was searched from year 2000 till November 30, 2020, using relevant Mesh terms, ('airway US' OR (('airway'/exp OR airway) AND ('US'/exp OR US))) AND ('endotracheal intubation'/exp OR 'endotracheal intubation') AND ('pediatric'/exp OR pediatric)" to Predict endotracheal tube size/placement in pediatric age (neonate till 18 years) by the US. Bibliographic cross-references of selected publications were further manually screened. The full texts of each article were studied, once the abstract was found appropriate independently by two reviewers. A total of 48 papers published between 2010 and 2020 were identified as relevant and read in detail. Average numbers of patients were 86 and total numbers of patients were 1978. Most of the studies included pediatric patients posted for elective surgeries under general anesthesia and excluded emergency procedures, known laryngeal or tracheal pathology, high-risk patients, recent upper respiratory tract infections or allergy to ultrasound gel. A total of 18 independent correlations were analyzed. Final combined r value calculated from all the included articles was 0.824 (95% CI 0.677, 0.908) with a P < 0.00001 {strong co-relation (r > 0.80)}. Q statistic of 756.484, and I2 statistics of 97.53% showed a large degree of heterogeneity in the effect size across the studies. Use of US for upper airway in pediatric patients is an effective modality and can effectively predict endotracheal tube size estimations in comparison to standard age-based or height-based formulae in the pediatric age group. US is a non-invasive, cost-effective, portable, and reproducible technique as compared to CT and MRI. It also takes less time with increasing expertise and experience.